Rechtstitel und Herrschaftssymbol : Studien zum Umgang der Empfänger in Italien mit Verfügungen Friedrichs II. (1194-1250) - Vogeler, Georg (2019)
This study investigates for the first time in detail the specific context for the use of documents prepared for recipients in Italy by the Staufer Frederick II (1198-1250). It compares the texts used for typical writings in communal Italy with the bureaucratic Regnum Siciliae, thereby addressing the issue of the function of written documents with a focus on the symbolic communication of authority.